Histopathological staging of atrophic lesions of gastric mucosa - Yang-kun Wang; Ying-ying Li; Bin Wang; Dong-mei Ran; Chao-ya Zhu; Ping Li; Bo Jiang; Su-nan Wang (Heliyon, 2024)
Objective: To study the histopathological staging of atrophic lesions of the gastric mucosa. Methods: Histology and immunohistochemistry were used to closely examine 2144 specimens of atrophic gastric mucosa that were taken from endoscopic biopsies. Results: When the gastric mucosa epithelium is affected by infection, chemical stimulation, immune factors, genetic factors, and other factors, it may cause an atrophy of gastric mucosa epithelium and a decrease in the number of glands, intestinal metaplasia, hyperplasia of smooth muscle fibers, and atrophy of stem cells in the proliferative zone. In this study, we characterized the above lesions as atrophic lesions of the gastric mucosa. Based on the morphological and histological characteristics of the lesion, as well as the law of cell proliferation and transformation during its occurrence and development, we propose five stages. We also noted the onset age, gender correlation, and histopathological characteristics of each stage of gastric mucosal atrophies. Conclusion: Understanding the pathological staging of gastric mucosal atrophy is essential for treating patients correctly and keeping track of changes in malignant cells. It is also very important in preventing the initiation of gastric cancer or from getting worse.